2020
DOI: 10.1186/s13054-020-03366-8
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin clearance with continuous veno-venous hemodialysis using high cutoff dialyzer versus continuous veno-venous hemodiafiltration using high-flux dialyzer: a prospective randomized controlled trial

Abstract: Background Myoglobin clearance in acute kidney injury requiring renal replacement therapy is important because myoglobin has direct renal toxic effects. Clinical data comparing different modalities of renal replacement therapy addressing myoglobin clearance are limited. This study aimed to compare two renal replacement modalities regarding myoglobin clearance. Methods In this prospective, randomized, single-blinded, single-center trial, 70 critically ill patients requiring renal replacement therapy were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 48 publications
2
43
0
5
Order By: Relevance
“…For instance, a previous study demonstrated higher IL-6 and IL-8 clearance by the EMiC2 filter than the standard membrane, but showed no significant impact on plasma cytokine concentrations [ 26 ]. Another study showed comparable IL-6 clearance between the EMiC2 and high-flux membrane [ 27 ]. Similarly, studies using the EMiC2 or HCO membranes reported no changes in plasma concentrations despite detectable clearance in the ultrafiltrate [ 11 , 15 , 28 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a previous study demonstrated higher IL-6 and IL-8 clearance by the EMiC2 filter than the standard membrane, but showed no significant impact on plasma cytokine concentrations [ 26 ]. Another study showed comparable IL-6 clearance between the EMiC2 and high-flux membrane [ 27 ]. Similarly, studies using the EMiC2 or HCO membranes reported no changes in plasma concentrations despite detectable clearance in the ultrafiltrate [ 11 , 15 , 28 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heyne et al [ 12 ] described this approach in a case series with an effective removal of myoglobin. Furthermore, Weidhase et al [ 13 ] recently published the results of a randomized trial, where a higher myoglobin clearance can be seen in patients treated with HCO dialyzers in contrast to the typically used high-flux dialyzers. Both had the same surface area of 1.8 m 2 and myoglobin clearance was about 8–10 ml/min for HCO dialyzers and 2–3 ml/min for high-flux dialyzers.…”
Section: Introductionmentioning
confidence: 99%
“…Weidhase et al recently published a randomized controlled trial comparing two renal replacement modalities regarding myoglobin clearance [ 1 ]. The authors found superior myoglobin clearance with a high cut-off (HCO) dialyzer running in continuous veno-venous hemodialysis (CVVHD) mode compared to a standard, high-flux dialyzer running in continuous veno-venous hemodiafiltration (CVVHDF) mode [ 1 ], which is not surprising, given the properties of HCO membranes.…”
mentioning
confidence: 99%
“…Weidhase et al recently published a randomized controlled trial comparing two renal replacement modalities regarding myoglobin clearance [ 1 ]. The authors found superior myoglobin clearance with a high cut-off (HCO) dialyzer running in continuous veno-venous hemodialysis (CVVHD) mode compared to a standard, high-flux dialyzer running in continuous veno-venous hemodiafiltration (CVVHDF) mode [ 1 ], which is not surprising, given the properties of HCO membranes. HCO dialyzers were first used in intermittent hemodialysis with the aim of free light chains [ 2 ] and myoglobin removal [ 3 ], but have later also been used with continuous dialysis techniques, mainly with the aim of improving clearance of inflammatory cytokines.…”
mentioning
confidence: 99%
See 1 more Smart Citation